336 Right ventricular mechanics in patients affected by pulmonary valve stenosis, before and after percutaneous pulmonary angioplasty. (8th December 2021) - Sirico, Domenico; Spigariol, Giulia; Basso, Alessia; Reffo, Elena; Biffanti, Roberta; Cerutti, Alessia; Di Candia, Angela; Sabatino, Jolanda; Castaldi, Biagio; Salvo, Giovanni Di
Abstract: Aims: Pulmonary valve stenosis accounts for 6–9% of all congenital heart diseases. The main effect of this obstructive lesion is a rise in right ventricular pressure; this overload leads to multiple changes in shape, dimensions, and volume of the ventricle. The diagnosis is based on transthoracic echocardiography and invasive heart catheterization. Usually the stenosis is classified into mild, moderate, and severe based on pressure gradient between right ventricle and pulmonary artery and on the ratio between right ventricle and left ventricle systolic pressure. Percutaneous balloon valvuloplasty is the treatment of choice in severe pulmonary valve stenosis in patients of all ages; alternatively surgical valvotomy is an option in selected cases. The aim of this study is to evaluate the mechanical changes of the right ventricle in patients undergoing balloon pulmonary valvuloplasty using transthoracic and speckle-tracking echocardiography (STE). Furthermore, we sought to investigate the correlation between haemodynamic and echocardiographic parameters to better evaluate the degree of pulmonary valve stenosis before and after treatment. Methods and results: Forty-three pediatric patients (19 males), mean age 3.2 ± 4.9 years with severe pulmonary valve stenosis and indication for percutaneous balloon valvuloplasty were recruited at the University Hospital of Padua. All patients underwent standard transthoracic echocardiography (TTE), STE with analysis of right ventricle global longitudinal strain (RVGLS) one day before and one day after the procedure. For each patient were collected invasive parameters during the interventional procedure before and after balloon valvuloplasty. After the procedure, there was an immediate statistically significant reduction of both peak-to-peak transpulmonary gradient (Dp post) and ratio between the systolic pressure of right and left ventricle (RV/LV ratio) with a drop of 29.3 ± 14.67 mmHg and 0.43 ± 0.03, respectively. Post-procedural echocardiography showed peak and mean transvalvar pressure gradient drop (50 ± 32.23 and 31 ± 17.97, respectively). The degree of pulmonary valve regurgitation was mild in 8% of patients before the procedure, following the intervention it reached 29% with a statistically significant increase ( P = 0.007). However, the incidence of pulmonary valve moderate and severe regurgitation remained stable after the procedure. The analysis of right ventricular function and mechanics showed a significant improvement of Fractional Area Change (FAC) immediately after the procedure (40.11% vs. 44.42%, P = 0, 01). On the other hand, right ventricular longitudinal systolic function parameters, TAPSE ( P = 0.60) and longitudinal strain ( P = 0.31), did not improve significantly after intervention. Finally, pre-procedural invasive RV/LV ratio showed good correlation to echocardiographic transvalvular peak and mean pressure gradient ( R = 0.375, P = 0.019 and R = 0.40, P = 0.012, respectively), as well as with FAC ( R = 0.31, P = 0.05), TAPSE ( R = 0.62, P < 0.001), and RVGLS ( R = 0.46, P = 0.01). Conclusions: Percutaneous balloon pulmonary valvuloplasty represents an efficient and safe procedure to relieve severe pulmonary valve stenosis. Interestingly, the analysis of right ventricular mechanics on echocardiography demonstrated an immediate global systolic function improvement following afterload reduction. Conversely, longitudinal systolic function did not show improvement immediately after intervention, possibly due to the necessity of longer time to recover. Finally, invasive preprocedural RV/LV ratio demonstrated better correlation with echocardiographic evaluation of stenosis degree and right ventricular function compared to invasive peak-to-peak pressure gradient. Therefore, RV/LV ratio should be preferred for the assessment of pulmonary valve stenosis.